A critical revision of the Andrena Fabricius, 1775 of India, with the description of two new species (Hymenoptera: Andrenidae) from Uttarakhand - Gautam, R.K.; Uniyal, V.P.; Wood, Thomas J. (European Journal of Taxonomy, 2024)
India is a large country in Asia, and covers the transition zone between the Palaearctic and Indomalayan biogeographic realms, with influences from both. Present in India are members of the genus Andrena, an enormous bee genus distributed predominantly throughout the Holarctic, with the greatest Indian diversity in the Himalayan region due to its Palaearctic influences. Despite early studies in the late 19th and early 20th centuries, there has been almost no work on this group in India during the past century. A revision of type and non-type museum material combined with new collections has produced a revised total of 36 species of Andrena for India, including 11 species reported for the first time as well as the newly described Andrena (Melandrena) kedarnatha Wood & Gautam sp. nov. (northern India and Nepal) and Andrena (Simandrena) tungnatha Wood & Gautam sp. nov. (northern India). The true holotype of A. (Euandrena) communis Smith, 1879 is definitively located. Andrena burkelii Bingham, 1908 is synonymised with A. (Pallandrena) morosa Cameron, 1897. Lectotypes are designated for A. (Euandrena) murreensis Cockerell, 1923 and A. (incertae sedis) comberima beharica Cockerell, 1920. Further comments are made on the status of Andrena taxa described from India for which type material is and is not currently available. Thirty additional Andrena taxa suggested as present in the Indian fauna are excluded as either erroneous or lacking supporting data. These results illustrate the extent to which study of the Indian Andrena fauna has been confused, and provide a more stable taxonomic base for future studies in this country.